Studies of the Mechanism of Adhesion of Polymer Coatings on the Oxidized Surface of Aluminum and Magnesium Alloys (Global Journals of Research in Engineering, 2024)
The adhesion of the polymer paint Lakroten E-244 was investigated on oxidized aluminum A5154 and magnesium MA-20 alloys It is shown that the adhesion of the polymer coating on the chemically oxidized surface of the aluminum alloy is significantly greater than on the anodic film of the magnesium alloy Using photoelectron XPS spectroscopy and SEM analysis the chemical composition and morphology of the alloys have been investigated The dependence of these factors on the adhesion force of the polymer coating to the oxidized surface of aluminum and magnesium alloys has been established Methods of modification of conversion coatings with ethylen glycol which significantly improve the adhesion of polymer layers have been proposed The chemical composition and morphology of these coatings have been investigated An explanation of the mechanism of improvement of adhesion properties of modified coatings on aluminum and magnesium alloys is given The mechanism of improving the adhesive properties of modified coatings on aluminum and magnesium alloys is explained
Keywords: adhesion strength; x-ray photoelectron spectroscopy; conversion coatings; paints